SOLITON SOLUTIONS FOR KUDRYASHOV-SINELSHCHIKOV EQUATION - Yusuf, Abdullahi; İnç, Mustafa; Bayram, Mustafa (Yildiz Technical Univ, 2019)
This paper acquires the closed form solutions for the Kudryashov-Sinelshchikov (KS) equation. The Riccati-Bernoulli (RB) sub-ODE method is used to acquire such solitons whose structure include trigonmetric, hyperbolic and algebraic structures. Some interesting figures for the obtained solutions are presented in order to shed light on the characteristics of the solutions.
Keywords: KS equation; RB sub-ODE method; soliton